Reconstruction, segmentation, and analysis of medical images : first International Workshops, RAMBO 2016 and HVSMR 2016, held in conjunction with MICCAI 2016, Athens, Greece, October 17, 2016, Revised selected papers /: first International Workshops, RAMBO 2016 and HVSMR 2016, held in conjunction with MICCAI 2016, Athens, Greece, October 17, 2016, Revised selected papers. (2017) - Unknown
No abstract available